A guide to better teaching : skills, advice, and evaluation for college and university professors - Jahangiri, Leila (Rowman & Littlefield Publishers, 2012)
A Guide to Better Teaching is a self-help book that provides anyone teaching a college course with a thorough understanding of what it takes to be an effective teacher. Derived from the authors' extensive research, several interactive assessment tools are included that measure levels of effectiveness according to learner preferences. Each chapter is filled with detailed explanations, relevant stories, and action-driven tables that help them in understanding and applying skills. This book aims to enhance teaching skills by offering critical perspectives, practical suggestions, and techniques for improvement. Whether a new teacher, an adjunct faculty, or a seasoned professor, this comprehensive information can be used to analyze effectiveness or the effectiveness of others. The suggestions and the assessment tools are applicable to the entire spectrum of organizational leaders and managers, in education, government or industry whose work requires giving presentations or communicating in a public forum.